Using AutoCAD 2011 - Grabowski, Ralph (Clifton Park, NY : Delmar Cengage Learning, 2011)
From the Publisher: Thoroughly updated to AutoCAD 2011 this easy-to-understand essentials edition covers all aspects of AutoCAD fundamentals, from an introduction to computer hardware and AutoCAD software to learning to draw with objects, direct editing of objects, and plotting. Industry veteran Ralph Grabowski uses his step-by-step tutorials which speeds the process of learning the commands required for 2D drafting of single drawings. Using AutoCAD 2011 leads users quickly to proficiency utilizing the most current design capabilities of the software.
Includes index.
Keywords: Computer graphics